Factors Associated with Acute Respiratory Infections (ARI) Among Toddlers at PMB Ana Hasanah, Tangerang - Viedya Wildan; Hasta Sulistyaningrum; Yanasita Mafluha; Dhea Ayunanda; Tiara (International Journal of Psychology and Health Science, 2025)
The toddler period is a critical stage in human growth and development, as this phase is marked by rapid physical and cognitive progress. The most at-risk group is toddlers, with approximately 20–40% experiencing Acute Respiratory Infections (ARI). ARI is one of the leading causes of morbidity among toddlers. This study aimed to determine the factors associated with the incidence of ARI in toddlers. The research used an analytical design with a cross-sectional approach. A total of 36 respondents were selected using the Slovin formula. The research instrument was a questionnaire. Data were analyzed using univariate and bivariate analyses with the chi-square test. The results showed that the majority of toddlers experienced ARI (80.6%), respondents with low education accounted for 55.6%, those not exclusively breastfed 66.7%, with a history of low birth weight (LBW) 72.2%, incomplete immunization 52.8%, poor maternal knowledge 41.7%, and good knowledge 19.4% (7 respondents). Statistical tests showed significant associations between maternal education (p=0.021), exclusive breastfeeding (p=0.029), history of LBW (p=0.010), immunization status (p=0.030), and maternal knowledge (p=0.017) with ARI incidence in toddlers. It is concluded that there are significant relationships between maternal education, exclusive breastfeeding, history of LBW, immunization status, and maternal knowledge with ARI among toddlers. It is recommended to improve knowledge regarding ARI prevention through health education programs.